Auditing Climate-Related Risk: Challenges to Auditor Independence and Professional Skepticism - Edy Susanto; Tenriwaru Tenriwaru; Ummu Kalsum (Jurnal Akuntansi, Keuangan, dan Manajemen, 2026)
Purpose: This study examines how climate-related risk is identified and assessed in financial statement audits and analyzes its implications for auditor independence and professional skepticism within a risk-based auditing framework in regional Public Accounting Firms in Indonesia. Methodology: This qualitative exploratory study was conducted through semi-structured interviews with four auditors from regional Public Accounting Firms in Makassar, Indonesia, each with a minimum of three years of audit experience. Document analyses of International Standard on Auditing (ISA) 200, ISA 315, and ISA 540 complemented the interviews. Thematic analysis was employed to identify recurring patterns in risk assessment, professional judgements, and responses to climate-related uncertainty. Results: The findings reveal three dominant themes: (1) climate-related risk is primarily incorporated into the entity-level risk assessment stage; (2) its classification as a material misstatement risk remains inconsistent; and (3) climate-related accounting estimates significantly increase reliance on management assumptions, thereby intensifying challenges to auditor independence and professional skepticism. The integration of climate risk remains largely principle-based and dependent on judgment rather than on structured technical guidance. Conclusions: This study demonstrates that climate-related risk reshapes inherent risk assessment and expands the behavioral dimensions of auditing practice in regional contexts. The findings highlight the need for more operational guidance to support the consistent integration of climate considerations within risk-based auditing. Limitations: This study is limited to a small sample of regional auditors and relies on qualitative perceptions. Contributions: This research contributes to auditing literature by empirically illustrating how climate-related risk affects professional judgment, independence, and skepticism in emerging regional audit environments.